Content Management in Digital Platforms for Migrants: Humberto Mendieta Torres - Mendieta Torres, Humberto (Quórum Académico, 2024)
The general objective of this research was to analyze content management in platforms for migrant citizens around the world. The theoretical foundation was based on authors such as Bramscher (2006), Carballo (2007), Cox and Yeadon (2002), Alonso (2011), Jurado and Martos (2022), Pérez and García (2016), Camus (2009), among others. Descriptive research was used, with documentary design. The sample consisted of four (4) administrators of digital platforms for migrants, which were also analyzed. The data collection technique was the qualitative interview to these administrators and the content analysis of their respective pages. Among the results and conclusions, it is highlighted that content management in the observed platforms applies a comprehensive strategy that combines the creation of relevant content with the active participation of the community. By understanding the needs and expectations of migrants, these platforms facilitate access to useful information and promote social integration.